Profitability of pairs trading in cryptocurrency market : Comparison of distance, cointegration, and copula methods - Liias, Otto (My University, 2023)
Pairs trading is a market-neutral trading strategy from the mid-1980s that aims to find linked underlying assets. Linkage is more commonly measured as the difference in normalized prices or through cointegration. Linkage can also be measured using, for example, copulas. In recent years, however, the returns from this strategy have been observed to decline due to, among other things, increased competition. However, cryptocurrencies are a relatively new asset class that has been identified as having inefficiencies and characteristics that could potentially generate profits in pairs trading. In this thesis, three different pairs trading methods are examined for their success in the cryptocurrency market. The methods investigated are distance, cointegration, and copula methods. The time period studied is from March 2020 to the end of 2022. All three methods will be compared in parallel and the studies will be conducted using both daily and hourly data. The pairs used for copula-based trading will be selected using Kendall's tau in addition to the two previous methods, distance and cointegration. In addition, the results are tested using different trading thresholds, stop-loss levels, and transaction costs and compared with a traditional buy and hold strategy. The study should provide insights into the efficiency of the cryptocurrency market. The results of the studies showed that the distance method performed the worst of the methods tested and was loss-making. In terms of monthly returns, the copula methods managed to produce the highest profit on both daily and hourly data. However, the cointegration method produced the highest profit per individual trade. Thus, after adding transaction costs, the cointegration method was the only profitable trading strategy on daily data. All methods were loss-making with transaction costs when using hourly data. The distance method showed a deterioration with tighter trading thresholds. Cointegration, on the other hand, showed an improvement with tighter trading thresholds. For the cointegration method on hourly data, when the trading threshold was set at 5, 6, or 7 instead of the original standard deviation of 2, the method was able to produce statistically significant returns even after transaction costs. Of the copula methods, only the distance-based and tau-based methods improved with tighter trading limits when using hourly data. The addition of stop-loss levels improved the performance of the distance method and worsened the performance of the cointegration method. Drawing reliable conclusions from the results is challenging for cointegration, as the results from daily data suffer from a lack of statistical significance and with hourly data the method only proved to be viable when the trading threshold was adjusted to a relatively high level ex post. However, due to intensive trading, the copula methods proved incapable of profitable trading that covered transaction costs. The use of hourly data generally produced worse results compared to daily data. However, the results did not clearly show the inefficiency of the cryptocurrency market while not excluding it.

Parikaupankäynti on markkinaneutraali kaupankäyntistrategia 1980-luvulta, jossa on tarkoituksena löytää toisiinsa linkittyneet kohde-etuudet. Linkittyneisyyttä mitataan tavallisemmin normalisoitujen hintojen erotuksena tai yhteisintegraatiolla. Linkittyneisyyttä voidaan mitata myös käyttäen esimerkiksi kopuloita. Viime vuosina strategian tuottojen on kuitenkin havaittu laskeneen muun muassa kilpailun lisääntymisen johdosta. Kryptovaluutat ovat kuitenkin suhteellisen tuore omaisuusluokka, jossa on havaittu tehottomuuden piirteitä ja ominaisuuksia, jotka potentiaalisesti voisivat tuottaa voittoa parikaupankäynnissä. Tässä pro gradu -työssä tutkitaan kolmen eri parikaupankäyntimetodin menestymistä kryptovaluuttamarkkinoilla. Tutkittavat metodit ovat etäisyys-, yhteisintegraatio- ja kopulametodi. Tutkittava aikajakso on maaliskuusta 2020 vuoden 2022 loppuun. Kaikkia kolme metodia vertaillaan rinnakkain ja tutkimukset toteutetaan sekä päivä- että tuntidataa käyttäen. Kopulapohjaisessa kaupankäynnissä käytettävät parit valitaan kahden aikaisemman metodin, etäisyys- ja yhteisintegraatiometodin, lisäksi Kendallin tauta hyödyntäen. Lisäksi tuloksia testataan eri kaupankäyntikynnyksiä ja stop-loss tasoja hyödyntäen, transaktiokustannusten kanssa sekä vertailemalla perinteiseen osta ja pidä -strategiaan. Tutkimuksen pohjalta on tarkoitus saada tietoa kryptovaluuttamarkkinoiden tehokkuudesta. Tutkimuksista saadut tulokset osoittivat etäisyysmetodin suoriutuvan testattavista menetelmistä huonoiten ja tuottavan tappiota. Kuukausittaisella tuotolla mitattuna kopulametodit onnistuivat tuottamaan eniten voittoa sekä päivä- että tuntidatalla. Yhteisintegraatiometodi tuotti kuitenkin eniten voittoa yksittäistä kauppaa kohden. Näin ollen transaktiokustannusten lisäämisen jälkeen yhteisintegraatiometodi oli ainoa voitollinen kaupankäyntistrategia päivädataa käytettäessä. Kaikki metodit olivat transaktiokustannusten kanssa tappiollisia tuntidataa käytettäessä. Etäisyysmetodi osoitti huononevansa tiukemmilla kaupankäyntikynnyksillä. Yhteisintegraatio taas osoitti päinvastoin paranevan tiukemmilla kaupankäyntikynnyksillä. Kun yhteisintegraatiometodin kohdalla tuntidataa käytettäessä kaupankäyntikynnys asetettiin aikaisemman 2 keskihajonnan sijasta tasolle 5, 6 tai 7, metodi kykeni kuitenkin tuottamaan tilastollisesti merkitseviä tuottoja transaktiokustannusten jälkeenkin. Kopulametodeista ainoastaan tuntidataa käytettäessä etäisyys- ja tau-pohjainen metodi paranivat tiukemmilla kaupankäyntikynnyksillä. Stop-loss tasojen lisääminen paransi etäisyysmetodin ja huononsi yhteisintegraation suoriutumista. Luotettavien johtopäätösten tekeminen tuloksista on haasteellista yhteisintegraation osalta, koska päivädatalla tulokset kärsivät tilastollisen merkitsevyyden puutteesta ja tuntidatalla metodi osoitti olevansa kannattava vasta kun kaupankäyntikynnys säädettiin jälkikäteen melko korkeaksi. Kopulametodit kuitenkin osoittivat intensiivisen kaupankäynnin takia olevansa kykenemättömiä transaktiokustannukset kattavaan kannattavaan kaupankäyntiin. Tuntidatan hyödyntäminen tuotti yleisesti ottaen huonompia tuloksia verrattuna päivädataan. Tulokset eivät selkeästi osoittaneet kryptovaluuttamarkkinoiden tehottomuutta sitä kuitenkaan poissulkematta.
Keywords: Pairs trading, cryptocurrency, distance, cointegration, copula